2021
DOI: 10.1080/19490976.2021.1907271
|View full text |Cite
|
Sign up to set email alerts
|

Completion of the gut microbial epi-bile acid pathway

Abstract: Bile acids are detergent molecules that solubilize dietary lipids and lipid-soluble vitamins. Humans synthesize bile acids with α-orientation hydroxyl groups which can be biotransformed by gut microbiota to toxic, hydrophobic bile acids, such as deoxycholic acid (DCA). Gut microbiota can also convert hydroxyl groups from the α-orientation through an oxo-intermediate to the β-orientation, resulting in more hydrophilic, less toxic bile acids. This interconversion is catalyzed by regio- (C-3 vs. C-7) and stereosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 88 publications
(169 reference statements)
0
25
0
1
Order By: Relevance
“…Based on the findings by Edenharder and Pfutzner, C. paraputrificum 12β-HSDH behaves in a similar manner to established 12α-HSDHs, as shown by its pH optimum and molecular weight. The gene encoding the 12β-HSDH in C. paraputrificum was recently identified, allowing for investigation into the diversity of potential 12β-HSDH producers [ 86 ]. Putative 12β-HSDH genes were found across Firmicutes, Actinobacteria, and Alphaproteobacteria.…”
Section: Oxidation and Epimerizationmentioning
confidence: 99%
“…Based on the findings by Edenharder and Pfutzner, C. paraputrificum 12β-HSDH behaves in a similar manner to established 12α-HSDHs, as shown by its pH optimum and molecular weight. The gene encoding the 12β-HSDH in C. paraputrificum was recently identified, allowing for investigation into the diversity of potential 12β-HSDH producers [ 86 ]. Putative 12β-HSDH genes were found across Firmicutes, Actinobacteria, and Alphaproteobacteria.…”
Section: Oxidation and Epimerizationmentioning
confidence: 99%
“…Microbial–host interactions closely influence human health status ( 1 , 2 ). Microorganisms colonizing the human body can participate in the synthesis and metabolism of vitamins, proteins, and lipids, promote immunity, maintain the local ecological balance in organs, degrade nutrients, provide energy to the host ( 1 , 3 , 4 ) and have an important impact on host metabolic processes. In contrast, oral microbiota have gradually gained importance as easily detectable colonizing microorganisms, and research has shifted from oral diseases to a broader perspective, of which tongue-coating microbiota are an important part.…”
Section: Introductionmentioning
confidence: 99%
“…Our research indicated that NMT reversed deoxycholic acid (DCA) level that was negatively correlated with ( Clostridium ) _innocuum_group and Faecalitalea , and positively correlated with ( Eubacterium ) _nodatum_group , Candidatus_Saccharimonas , and Lachnospiraceae_UCG-006 ( Figure 6 ). Bile acids (BA) are synthesized from cholesterol in the liver and most secreted into the intestinal lumen, where a substantial mass of toxic-hydrophobic bile acids was transformed, such as DCA ( Nicholson et al, 2012 ; Doden et al, 2021 ). Recently, destruction of the intestinal barrier which correlated with secondary bile acids has been reported ( Pi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%